1994
DOI: 10.1002/polb.1994.090321505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polymerization catalysts on the microstructure of P(LLA‐co‐εCL)

Abstract: SYNOPSISThe copolymerization of L,L-lactide and c-caprolactone was carried out using antimony trioxide and stannous octoate as catalysts. The effect of polymerization catalysts on the physical and the chemical microstructures of this copolymer was investigated by 13C NMR and DSC analysis. Antimony trioxide causes more random sequence distribution within the copolymer chain due to its higher transesterification characteristic than stannous octoate. The copolymer samples made with the antimony trioxide catalyst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 13 publications
(1 reference statement)
2
23
0
Order By: Relevance
“…The ratio of the integrated intensity at 5.2 ppm (the methyne group of LLA unit) to that at 4.1 ppm (the ␥-methylene group of CL neighbouring oxygen of ester bond) 16,26 was used to determine the chemical composition of the copolymer. w L was calculated from eq.…”
Section: Measurements and Observationmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio of the integrated intensity at 5.2 ppm (the methyne group of LLA unit) to that at 4.1 ppm (the ␥-methylene group of CL neighbouring oxygen of ester bond) 16,26 was used to determine the chemical composition of the copolymer. w L was calculated from eq.…”
Section: Measurements and Observationmentioning
confidence: 99%
“…18 Recently, Choi et al also showed that P(LLA-CL) synthesized using stannous octoate were semicrystalline and of block-type in the entire range of monomer mixing. 26 Seppä lä et al synthesized P(LLA-CL) of different LLA contents using stannous octoate and investigated the change of physical properties during aging in phosphate buffered solution, 11,12,29 and Grijpma and Pennings studied crystallization at room temperature for P(LLA-CL) (50/50) synthesized using tin catalyst. 7,19 These studies demonstrated that the P(LLA-CL) copolymers changed their physical properties during storage at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 gives typical methine regions in the 1 H NMR spectra of PLLA, PDLLA, and PLGA samples. The molar fraction of GA moiety in PLGA can be calculated from the integrated area of peaks at 5.15 ppm due to methine protons in LA units 17,29,30 and that of peaks at 4.60-4.90 ppm owing to methylene protons in GA blocks in PLGA. 7,9,15 Assigning I L to integrated peak area at 5.15 ppm, I G integrated Table II.…”
Section: Synthesis and Molecular Weights Of Copolymersmentioning
confidence: 99%
“…6,7 Therefore, the copolymerization of PLLA with PCL is known to be an effective route to improve properties in comparison with each individual component. 8,9 In a copolymer, when one block can crystallize, the physical properties and degradability of other blocks will be affected since the morphology can also be dramatically altered at the microscale level. [10][11][12] It has been conrmed that the PLLA-PCL copolymer is weakly segregated in the melt depend on composition, 13,14 and the melting and crystalline temperature of the PLLA block are higher than those of the PCL block.…”
Section: Introductionmentioning
confidence: 99%